Relationship between Family History, Age, Obesity and Smoking Habit with Hypertension Occurrence at Public Health Center Region Pahandut - Muhammad Syahibuddin Rifa’i; Ravenalla Abdurrahman Al Hakim Sampurna; Agnes Immanuela Toemon; Trilianty Lestarisa; Austin Carmelita Bertilova (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Hypertension is cardiovascular disease that affected 22% people in the total world population. In Indonesia hypertension prevalence according to riskesdas 2018 reaches 34,11%. Hypertension occurs insperable from its risk factor. The purpose of this study is to analyze the relationship between family history, age, obesity, and smoking habits with the occurrence of hypertension in the region of the Public health center, Pahandut. in 2022. This research method uses a cross-sectional approach, with large of 100 samples and use purposive sampling thecnique. Data Analyzed using Chi-square test. The results of the bivariate analysis obtained variables related to the occurrence of hypertension are family history (p-value= 0,000), age (p-value= 0,000), obesity (p-value= 0,048) and smoking habit (p-value= 0,001). This study concludes that there is a relationship between family history, age, obesity, and smoking habits with the occurrence of hypertension in the region of the Public health center, Pahandut. in 2022